2007
DOI: 10.1038/ncb1574
|View full text |Cite
|
Sign up to set email alerts
|

C. elegans mitochondrial factor WAH-1 promotes phosphatidylserine externalization in apoptotic cells through phospholipid scramblase SCRM-1

Abstract: Externalization of phosphatidylserine, which is normally restricted to the inner leaflet of plasma membrane, is a hallmark of mammalian apoptosis. It is not known what activates and mediates the phosphatidylserine externalization process in apoptotic cells. Here, we report the development of an annexin V-based phosphatidylserine labelling method and show that a majority of apoptotic germ cells in Caenorhabditis elegans have surface-exposed phosphatidylserine, indicating that phosphatidylserine externalization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
110
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(118 citation statements)
references
References 25 publications
7
110
0
1
Order By: Relevance
“…18 WAH-1 turned out to collaborate with another mitochondrial factor, CPS-6 (the nematode ortholog of endonuclease G), which reportedly co-translocates with WAH-1 to the nucleus where the WAH-1-CPS-6 complex mediates DNA degradation, 18 as well as with the phospholipid scramblase SCRM-1, a plasma membrane protein that favors the exposure of phosphatidylserine (PS) on the surface of apoptotic cells. 19 These observations were in line with the facts that AIF can acquire a nuclease function in mammals and yeast cells (by interacting with proteins from the cyclophilin family), 20 and can stimulate PS exposure in murine cells 17 (Figure 1). These results indirectly revealed the importance of MOMP (which is required for the release of WAH-1/AIF and CPS-6/endonuclease G from the mitochondrial intermembrane space) in the developmental cell death program of C. elegans.…”
Section: The 'Core' Machinery For Cell Death Executionsupporting
confidence: 72%
“…18 WAH-1 turned out to collaborate with another mitochondrial factor, CPS-6 (the nematode ortholog of endonuclease G), which reportedly co-translocates with WAH-1 to the nucleus where the WAH-1-CPS-6 complex mediates DNA degradation, 18 as well as with the phospholipid scramblase SCRM-1, a plasma membrane protein that favors the exposure of phosphatidylserine (PS) on the surface of apoptotic cells. 19 These observations were in line with the facts that AIF can acquire a nuclease function in mammals and yeast cells (by interacting with proteins from the cyclophilin family), 20 and can stimulate PS exposure in murine cells 17 (Figure 1). These results indirectly revealed the importance of MOMP (which is required for the release of WAH-1/AIF and CPS-6/endonuclease G from the mitochondrial intermembrane space) in the developmental cell death program of C. elegans.…”
Section: The 'Core' Machinery For Cell Death Executionsupporting
confidence: 72%
“…Most obviously, neither MOMP nor cytochrome c plays a role in initiation of apoptosis in the nematode, although the mitochondrially localized proteins CPS-6 and WAH-1 (nematode homologs of mammalian endonuclease-G and AIF, respectively) have been suggested to contribute to DNA degradation and phosphatydilserine externalization later in the apoptotic program. [16][17][18][19] As noted, CED-4 lacks the WD-domain repeats present in APAF-1 that are necessary for cytochrome c binding, and the release of CED-4 from sequestration by CED-9 appears to be sufficient to cause formation of the nematode apoptosome. Furthermore, despite early reports to the contrary 20,21 it is now accepted that mammalian Bcl-2 homologs do not functionally interact with APAF-1.…”
Section: Nematodes: Like Us Only Differentmentioning
confidence: 99%
“…Phosphatidylserine exposure on the outer membrane leaflet is a conserved feature of apoptosis, and recognized by mammalian macrophage and during corpse engulfment in C. elegans. [16][17][18][19] The so-called psr gene was identified by expression-cloning the target of an engulfment-blocking antibody, 20 but is now thought to encode a nuclear protein, and recent studies have convincingly demonstrated that it is not required for corpse engulfment by either mouse fibroblasts or Drosophila hemocytes. 21,22 Meanwhile, other mechanisms of recognizing phosphatidylserine have been uncovered in mammals.…”
Section: Eat To Competementioning
confidence: 99%